Home Surveillance System Based on Internet of Things and Thermal Sensors - Rizal Tjut Adek; Munirul Ula; Bustami; Syibbran Mulaesyi; Muhammad Bayu Juhri (LPPM Universitas Malikussaleh, 2022)
A home security system's primary purpose is to protect and monitor areas that are vulnerable to intruders. The cameras can continuously monitor location; however, it’s had drawbacks such as high installation costs, significant electricity consumption, high memory space utilization of the recording system, and complexity of the hardware circuits, in low light condition it need a night vision camera to obtain clear images. The purpose of the research, is to develop a prototype of surveillance system that uses the PIR sensor and night vision camera to detected intruder in low light condition. The methodology used in this research is prototyping. It started with objectives determination of surveillance system, develop, refine and demonstrate the hardware and software, testing and implement the system. The Arduino Board, programmable Arduino IDE microcontroller, battery, RF module, camera, WIFI module, NodeMCU and PIR sensor are all included in this prototype. An application will be loaded on the user's android device, which will be utilized as the security system monitoring and controller. The WIFI module allows remote control by connecting the system to the internet via the cloud. A PIR sensor will be used to monitor the temperature around for the detecting the presence of human. If the sensor detects the thermal imaging, it will trigger the night vision camera to record. The result of the system testing, shows that the system was working perfectly. The testing on camera operability shows that the night vision camera gets a clear image at maximum 10 m. The limitations of this system are unable to detect the thermal objects at more than 10 m clearly. This weakness can be improved by more complete hardware in future research.